Imposex in Thais rustica (Mollusca: Neogastropoda) (Lamark, 1822) as an indicator of organotin compounds pollution at Maceio coast (Northeastern Brazil) (Brazilian Journal of Oceanography, 2004)
The use of OTC (organotin compounds) as biocides in naval antifouling paints causes impacts on non-target organisms. One of these impacts is a syndrome called imposex in gastropod molluscs. Imposex is the imposition of male secondary sexual characteristics in female gastropods as result of endocrine disruption. In this preliminary study, imposex was observed in four out of ten sampled stations in Maceió: the city Port (100% females exhibited imposex), the Marine Emissary (23% females exhibited imposex), the Marine Terminal (35% females exhibited imposex) and Saco da Pedra beach (12% females exhibited imposex). These stations were distributed in a NE-SW orientation from the Port southwards along the coastline, following the general circulation pattern of the area. The low values of VDSI, RPSI and RPLI indicate that Maceió Coast is a less contaminated area, probably because of low shipping activities together with the fact that the sampling zone is an open coastal system and not an enclosed bay. These results suggest that the imposex development in Thais rustica may be used as a biological indicator of OTC pollution.